1987
DOI: 10.2330/joralbiosci1965.29.738
|View full text |Cite
|
Sign up to set email alerts
|

Sixth and seventh cusp on lower molar teeth of Malawians in East-Central Africa.

Abstract: Abstract:The expressions of both sixth cusp (C6) and seventh cusp (C7) among the Malawians in East-Central Africa are described and compared with those of other African, Mongoloid, and Caucasoid populations.The subjects consisted of 99 males and 95 females. Scoring was performed using dental hard stone casts according to Turner's standard plaques. Asexual dimorphism in the occurrence of each trait was found to be not significant by chi-square test. The frequency of C6 in Malawians is remarkably lower than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Except for midline diastema, each trait is part of the Arizona State University Dental Anthropology System (ASUDAS) (Turner et al, 1991); all are documented to be largely independent of one another, based on the genetic investigation of Nichol (1990). Procedures used in ASU-DAS are based on well-established criteria for scoring intratrait variation, and proved reliable in many preceding studies (Scott, 1973(Scott, , 1980Turner, 1985aTurner, , 1987Turner, , 1992Sakuma and Ogata, 1987;Haeussler et al, 1988;Turner and Markowitz, 1990;Irish and Turner, 1990;Irish, 1993Irish, , 1994Irish, , 1997Irish, , 1998aIrish, -d, 2000Jackes et al, 2001). Traits are recorded with the aid of 23 rank-scale reference plaques to help standardize scoring (Turner et al, 1991).…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Except for midline diastema, each trait is part of the Arizona State University Dental Anthropology System (ASUDAS) (Turner et al, 1991); all are documented to be largely independent of one another, based on the genetic investigation of Nichol (1990). Procedures used in ASU-DAS are based on well-established criteria for scoring intratrait variation, and proved reliable in many preceding studies (Scott, 1973(Scott, , 1980Turner, 1985aTurner, , 1987Turner, , 1992Sakuma and Ogata, 1987;Haeussler et al, 1988;Turner and Markowitz, 1990;Irish and Turner, 1990;Irish, 1993Irish, , 1994Irish, , 1997Irish, , 1998aIrish, -d, 2000Jackes et al, 2001). Traits are recorded with the aid of 23 rank-scale reference plaques to help standardize scoring (Turner et al, 1991).…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…All traits were previously found to be largely independent of one another (Nichol, 1990). ASUDAS procedures are based on well-established criteria for scoring intratrait variation, and proved reliable in many preceding studies (e.g., Scott, 1973Scott, , 1980Turner, 1985aTurner, , 1987Turner, , 1992Sakuma and Ogata, 1987;Sakuma et al, 1991;Haeussler et al, 1988;Turner and Markowitz, 1990;Irish and Turner, 1990;Irish, 1993Irish, , 1994Irish, , 1997Irish, , 1998aIrish, -d, 2000Jackes et al, 2001). Traits are recorded using 23 rank-scale reference plaques that help standardize scoring by providing representations of minimum, maximum, and common intermediate expressions (Turner et al, 1991).…”
Section: Dental Trait Recordingmentioning
confidence: 99%
“…This cusp occurs not only in modern human populations but also in fossil hominids (Gregory and Hellman, 1926;von Koenigswald, 1952b) and nonhuman hominoids (Selenka, 1898). Sakuma and Ogata (1987) demonstrated that the seventh cusp occurs more frequently in Africans than non-Africans.…”
Section: Sixth Cusp: Lm1mentioning
confidence: 99%